Climate-Resilient and Low-Carbon Transport in Sub-Saharan Africa : A Contribution to the Africa Climate Business Plan - World Bank (World Bank, Washington, DC, 2017)
The objective of this transport component of the broader Africa Climate Business Plan (ACBP) is to begin to mainstream climate benefits into the World Bank’s transport program for Sub-Saharan Africa, the better to assist African countries in bringing their climate change efforts to scale. It is a first step towards mainstreaming responses to the climate challenge into transport programs in Africa, and it represents the first time the Transport & ICT GP has produced a work plan for its investment and technical assistance operations that takes into account the content of countries’ Nationally Determined Contributions (NDCs) and attempts to align World Bank support to the goals stated therein. The transport work plan under this Africa Climate Business Plan will consist of up to $3.2 billion in investments and technical assistance over the 2016-2020 period – including $2.8 billion in World Bank funds. Those investments will help to make progress on two strategic objectives: (1) improving the resilience of African transport infrastructure to climate change by defining four pillars of resilient transport; and (2) improving the carbon-efficiency of transport systems in Sub-Saharan Africa.